Fungal Degradation of Cellulosic Materials used as Support for Cultural Heritage - Mallo, Andrea Cecilia (2017)
A great part of the cultural heritage of humanity available in museums and libraries is stored in paper. However, this main support used from early civilization times is a biomaterial susceptible to deterioration by fungal transformation. Two fungal phenomena, cellulose degradation and synthesis of secondary metabolites, are responsible for paper deterioration. Thus, the understanding of fungal deterioration pathways is key to improve the durability of the cultural heritage in paper and develop new and adequate sustainable strategies of restoration. This review gives an approach about the current knowledge of cellulose transformation by fungi associated with paper and the mechanisms involved. Since several metabolites derived from fungi growing on paper, such as pigments, can deteriorate invaluable cultural heritage, knowledge on these metabolites is also fundamental to improve conservation strategies of historical documents.